A comparative study between NURBS surfaces and voxels to simulate the wear phenomenon in micro-EDM. Issue 6 (1st November 2016) - Surleraux, Anthony; Pernot, Jean-Philippe; Bigot, Samuel
ABSTRACT: The prediction of the tool wear phenomenon in the micro electro discharge machining technology would be of a great use in the optimization of tool shapes. In order to do so, the ability to rapidly and precisely simulate the process is required. The choice of a geometrical model for the electrodes is of the utmost importance as it will condition the available methods for the simulation. Two geometrical models have been tested and implemented: NURBS and voxels embedded in an octree data structure. A limited experimental validation has been conducted and the results compared to the simulation through the use of the Hausdorff metric. GRAPHICAL ABSTRACT: